TURKMAN TILIGA RUS TILIDAN O‘ZLASHGAN SO‘ZLAR - Babayeva, M.A. (SCIENCE and SOCIETY, 2022)
In the article, the period in which the borrowed words entered the Turkmen language, the assimilation of Russian words into the Turkmen language, the pronunciation and spelling of the borrowed words are observed. Linguistic differences are analyzed.